Deep Learning-Based Pathology Image Analysis Enhances Magee Feature Correlation With Oncotype DX Breast Recurrence Score - Li, Hongxiao; Wang, Jigang; Li, Zaibo; Dababneh, Melad; Wang, Fusheng; Zhao, Peng; Smith, Geoffrey H.; Teodoro, George; Li, Meijie; Kong, Jun; Li, Xiaoxian (Frontiers in Medicine, 2022)
Background: Oncotype DX Recurrence Score (RS) has been widely used to predict chemotherapy benefits in patients with estrogen receptor positive breast cancer. Studies showed that the features used in Magee equations correlate with RS. We aim to examine whether deep learning (DL)-based histology image analyses can enhance such correlations. Methods: We retrieved 382 cases with RS diagnosed between 2011-2015 from Emory University and Ohio State University. All patients received surgery. DL models were developed to detect nuclei of tumor cells and tumor-infiltrating lymphocytes (TILs) and segment tumor cell nuclei in hematoxylin and eosin (H&E) stained histopathology whole slide images (WSIs). Based on the DL-based analysis, we derived image features from WSIs, such as tumor cell number, TIL number variance, and nuclear grades. The entire patient cohorts were divided into one training set (125 cases) and two validation sets (82 and 175 cases) based on the data sources and WSI resolutions. The training set was used to train the linear regression models to predict RS. For prediction performance comparison, we used independent variables from Magee features alone or the combination of WSI derived image and Magee features. Results: The Pearson’s correlation coefficients between the actual RS and predicted RS by DL-based analysis were 0.7058 (p-value = 1.32×10-13) and 0.5041 (p-value = 1.15×10-12) for the validation set 1 and 2, respectively. The adjusted R2 using Magee features alone are 0.3442 and 0.2167 in the two validation sets, respectively. By contrast, the adjusted R2 values were enhanced to 0.4431 and 0.2182 when WSI-derived imaging features were jointly used with Magee features. Conclusions: Our results suggest that DL-based digital pathological features can enhance Magee feature correlation with RS.